Practice of Differentiated Instruction in Language learning Process: a Narrative Inquiry - Khadka, Rim Bahadur (Haimaprabha, 2026)
Teaching is for learning and learning becomes effective when the teachers provide a repertoire of activities that meet learners' needs. It is necessary to study and prepare documents on what sorts of activities are used in English language teaching in classrooms.This research explores the variety of activities English language teachers use in the classrooms. The main objectives of my study are to find secondary English language teachers' experience of providing activities and to find out the role of the ICT to support to differentiation of English language skills and aspects. My study is delimited to only modification of process (one component of differentiated instruction.I used narrative inquiry as a research method and personal stories of research participants as data. My research participants were one female and four male secondary English teachers who were engaged in teaching for ten to twenty years in government schools. Their teaching stories tell us how they differentiate their instruction in the meaning-making process. I used the Cognitive Load Theory of John Sweller to make the theoretical base of my study.  Based on the stories of the participants, the researcher discovered that differentiated instruction is an essential approach to be practiced in our classroom to address classroom diversity. Furthermore, it was found that English teachers in our area modified their instruction through group work, pair work, project work, question methods, no silent, and whole class activities to cater to the diverse needs of all learners and it was easier due to the ICT. Thus, it is concluded that the teachers variously differentiate their instruction with the help of ICT.